Філософія спілкування в контексті педагогічної культури - Пономарьов, Олександр Семенович (НТУ "ХПІ", 2012)
The role of philosophy of intercourse as a factor of forming and development of pedagogical culture is shown. Possibilities of dialogic intercourse in the increase of efficiency of education are exposed, in development of students professional and personality. The necessity of strengthening of their spiritual-cultural education in the system of forming of a new national elite is grounded.
Keywords: педагогічна культура; демократизація суспільного життя; філософія спілкування; філософія культури